Teaching history through memory: multiculturalism and the historical method - Costa, Marcos Ithalo de Souza (2022)
When analyzing contemporary society, it becomes clear that it undergoes numerous changes, such as a more intense and structured struggle for recognition and equity on the part of historically excluded social groups, evidencing our multicultural reality. At this juncture, history teachers must seek new methodologies, given that this subject is currently regarded as tedious and irrelevant by a significant percentage of students. Considering the distance of its contents from the social context of the students, when adopting traditional methodologies and tools. Thus, this paper aims to point out ways to revalue history by means of a qualitative and bibliographic methodology using a conceptual framework. As a source we utilize works that focused on methodologies of teaching history   through the use of lived experiences. As a result, we could conclude that presenting historical content relating it with personal memories of the students tends to foster critical thinking and a make history more approachable.